Pengaruh Strategi Directed Reading Thinking Activity (DRTA) terhadap Kemampuan Membaca Pemahaman Siswa Kelas V Sekolah Dasar - Sari, Putri Nina; Sukma, Elfia; Fitria, Yanti (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
The objective of this study is to find out the effect of using the strategy of directed reading thinking activity (DRTA) on the reading comprehension ability of 5th grade students in an elementary school. The type of research used in this study is in the form of   quasi-experimental design. The research design of this study is the non-equivalent posttest-only control group design. The research was conducted at SDN 15 Padang Sarai, Kota Padang. Based on the post-test results, the average value of reading comprehension ability of the control class is 71,18. The control class was treated with a conventional learning method. Through the implementation of the Directed Reading Thinking Activity (DRTA) strategy, the average value of reading comprehension ability in the experimental class is 80,30. Based on the hypothesis test and by using the t- test with significant level   it was obtained that the =  and   and with the    the H1 is therefore, accepted and  H0 is rejected.. thus, it is concluded that the directed reading thinking activity (DRTA) strategy significantly affects the reading comprehension ability the 5th grade students  Keyword: Strategy DRTA, Reading comprehension Ability